Sex Differences in the Effectiveness of First-Line Tumor Necrosis Factor Inhibitors in Psoriatic Arthritis: Results From the European Spondyloarthritis Research Collaboration Network - Hellamand, Pasoon; van de Sande, Marleen G H; Ørnbjerg, Lykke M; Klausch, Thomas; Eklund, Kari K; Relas, Heikki; Santos, Maria J; Vieira-Sousa, Elsa; Loft, Anne G; Glintborg, Bente; Østergaard, Mikkel; Lindström, Ulf; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2024)
OBJECTIVE: Women with psoriatic arthritis (PsA) may have reduced tumor necrosis factor inhibitor (TNFi) effectiveness compared to men. We examined sex differences in treatment response and retention rates during 24 months of follow-up among patients with PsA initiating their first TNFi. METHODS: Data from patients with PsA across 13 European Spondyloarthritis Research Collaboration Network registries starting their first TNFi were pooled. Logistic regression was used to analyze the association between sex and treatment response using low disease activity (LDA) according to the Disease Activity Score in 28 joints using the C-reactive protein level (DAS28-CRP) (<3.2) at six months as the primary outcome. Analyses were adjusted for age, country, conventional synthetic disease-modifying antirheumatic drug treatment, and TNFi start year. Retention rates were explored using the Kaplan-Meier estimator. RESULTS: We analyzed the treatment response of 7,679 patients with PsA (50% women) with available data on LDA at six months. At baseline, women and men had similar characteristics, including mean DAS28-CRP (women vs men, 4.4 [SD 1.2] vs 4.2 [SD 1.2]), though patient-reported outcome measures were worse in women. At six months, 64% of women and 78% of men had LDA (relative risk [RR] 0.82; 95% confidence interval [CI] 0.80-0.84). This difference was similar after adjustment (RR 0.83; 95% CI 0.81-0.85). TNFi retention rates were evaluated in 17,842 patients with PsA. Women had significantly lower retention rates than men at all time points (women 79%, 64%, and 50% vs men 88%, 77%, and 64% at 6, 12, and 24 months, respectively). CONCLUSION: Despite comparable disease characteristics at baseline, women with PsA have reduced treatment response and retention rates to their first TNFi, highlighting the need to consider sex differences in PsA research and management.
Keywords: Spondylarthritis; psoriatická artritida; Arthritis, Psoriatic; výsledek terapie; Tumor Necrosis Factor-alpha; mužské pohlaví; TNF-alfa; ženské pohlaví; Humans; antirevmatika; Sex Characteristics; spondylartritida; inhibitory TNF; Tumor Necrosis Factor Inhibitors; Antirheumatic Agents; pohlavní dimorfismus; Female; Treatment Outcome; lidé; Male